2019
DOI: 10.1186/s12864-019-5483-x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analysis of cytochrome P450 multigene family and their differential expression analysis in Solanum lycopersicum L. suggested tissue specific promoters

Abstract: BackgroundCytochrome P450 (P450) is a functionally diverse and multifamily class of enzymes which catalyses vast variety of biochemical reactions. P450 genes play regulatory role in growth, development and secondary metabolite biosynthesis. Solanum lycopersicum L. (Tomato) is an economically important crop plant and model system for various studies with massive genomic data. The comprehensive identification and characterization of P450 genes was lacking. Probing tomato genome for P450 identification would prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 70 publications
1
20
0
Order By: Relevance
“…This directly led to much less production of SLs in LA0716, IL6‐2 and IL6‐3, the cause for P. aegyptiaca resistance. Currently, based on the conserved motifs, 233 Sl P450 genes with tissue specific promoters have been identified from tomato genome and classified into nine clans 68 . By comparative analysis with these results, we found that Solyc06g073570 (SlCYP82W1) belonged to clan 71, and different from the identified SlCYP711A 48 and SlCYP722C 69 .…”
Section: Discussionmentioning
confidence: 91%
“…This directly led to much less production of SLs in LA0716, IL6‐2 and IL6‐3, the cause for P. aegyptiaca resistance. Currently, based on the conserved motifs, 233 Sl P450 genes with tissue specific promoters have been identified from tomato genome and classified into nine clans 68 . By comparative analysis with these results, we found that Solyc06g073570 (SlCYP82W1) belonged to clan 71, and different from the identified SlCYP711A 48 and SlCYP722C 69 .…”
Section: Discussionmentioning
confidence: 91%
“…Cytochrome P450s are evolutionarily conserved enzymes that are involved in the catalysis of numerous reactions, required for growth, development, defence [30] and secondary metabolism [31]. Prior to this study, no CYP450 genes had been identi ed, let alone characterized, in any species of the genus Fontainea.…”
Section: Discussionmentioning
confidence: 99%
“…The single-family clans restrict themselves from gene duplication, and the enzymes they include are highly conserved with essential functions. These clans are most likely to undergo negative selection [ 86 ]. CYP51 is considered to be one of the most conserved and the oldest eukaryotic CYP450s [ 80 ].…”
Section: Discussionmentioning
confidence: 99%